2002
DOI: 10.1177/009145090202900108
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Drug Use in Estonia: The Context of Club Culture

Abstract: Youth subcultures, the use of illicit drugs, and the relationship between the two were thoroughly influenced by the opening of Estonia to international influences in the 1990s. Survey data point at a recent growth in the use of illicit drugs among Estonian teenagers. Relying on participant observation and a number of in-depth individual and group interviews in 1997–2000, the article describes the “club” or “rave” culture in the Estonian capital. Consumption of illicit drugs belongs to that youth subculture as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 3 publications
0
15
0
3
Order By: Relevance
“…Sierosławski and Zielin´ski (2001) have, in their qualitative research in Poland, also concluded that cannabis users form a distinctive subculture and strictly separate themselves from those who use opiates. In a similar vein, the culture of using the fashionable ''entertainment drugs'' associated with club culture offers norms to regulate drug-use (Calafat et al 2001: 183--186;Allaste and Lagerspetz 2002).…”
Section: Patterns Of Drug Usementioning
confidence: 99%
See 1 more Smart Citation
“…Sierosławski and Zielin´ski (2001) have, in their qualitative research in Poland, also concluded that cannabis users form a distinctive subculture and strictly separate themselves from those who use opiates. In a similar vein, the culture of using the fashionable ''entertainment drugs'' associated with club culture offers norms to regulate drug-use (Calafat et al 2001: 183--186;Allaste and Lagerspetz 2002).…”
Section: Patterns Of Drug Usementioning
confidence: 99%
“…Also in Estonia, the synthetic drug users' subculture related with the club scene can be contrasted with the drug use of other more marginalised youth groups where opiates dominate. Their higher price and their connectedness to ''Western'' youth culture has made the ''new'' substances attractive to trend-conscious nightclubbers in Tallinn, the capital city (Allaste and Lagerspetz 2002), while a subculture of opiate injectors also continues to exist. Interestingly, different sources of information confirm that the overwhelming majority (80--97%) of the injecting opiate addicts receiving treatment in Estonia belong to the Russianspeaking minority, which makes up about a third of the country's population (Ahven 2000: 45;Vetik 2001: 10).…”
Section: Introductionmentioning
confidence: 99%
“…A current research project in Estonia has its starting point in this assumption, contrasting the synthetic drug users' subculture related with the club scene [22] with the drug use of other, mostly Russian-speaking youth groups, where injected opiates dominate. The youngsters differ from each other not only with respect to the drugs used, but also in their economic life chances and in their awareness of the risks their lifestyle exposes them to.…”
Section: Emergence Of Dual Drug Scenes?mentioning
confidence: 99%
“…I augusti 2002 skrev Airi-Alina Allaste och jag en gemensam kortare artikel på estniska om utvecklingen av estländsk drogpolitik (Lagerspetz & Allaste 2002). Jag är Airi-Alina tacksam för att hon tillät mig använda en del av de data som samlades in för den tidigare artikeln och särskilt för att hon under flera diskussioner delade med sig av sina synpunkter på estländsk drogkontroll.…”
Section: Mikko Lagerspetzunclassified
“…2 De nya syntetiska partydrogerna har snabbt spridits bland ungdomen i CÖE-regionen (t.ex. Allaste & Lagerspetz 2002) och uppkomsten av en "dubbel" drogscen med både svårt socialt marginaliserade och ickemarginaliserade delar har noterats i flera län-der (ibid., Sieroslawski & Zielinski 2001).…”
Section: Utvecklingen Av Drogpolitiken I Det åTer Självständiga Estlandunclassified